2016
DOI: 10.15406/aovs.2016.05.00156
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcomes after Pars Plana Vitrectomy for the Treatment of Epiretinal Membranes

Abstract: Purpose: To report the long-term outcomes of surgical treatment of epiretinal membranes (ERM) with pars plana vitrectomy (PPV) and internal limiting membrane (ILM) peeling.Methods: This was a retrospective interventional case series of patients with symptomatic ERM. 340 eyes of 322 patients were included in the study. Mean age of the sample was 68±12 years. Preoperative and postoperative Corrected Distance Visual Acuity (CDVA), as well as Intraocular Pressure (IOP) measurements were compared, Central Macular T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although preoperative values are highly varied among prior studies, they all demonstrated similar improvements with one year postoperative vision ranging between 0.180 and 0.690 logMAR (Snellen 20/30 to 20/100) and CMT 268-375µm. 9,10,[13][14][15] BCVA at five years was 0.109±0.029 logMAR (Snellen 20/25), which is better than another study reporting outcomes of ERM surgery with ICG visualization (0.449±0.487logMAR; Snellen 20/60). 2 Dawson et al demonstrated that surgical intervention on patients with better preoperative BCVA yields a better final BCVA and patients with poorer preoperative BCVA showed a greater change in BCVA following ERM surgery.…”
Section: Discussionmentioning
confidence: 53%
“…Although preoperative values are highly varied among prior studies, they all demonstrated similar improvements with one year postoperative vision ranging between 0.180 and 0.690 logMAR (Snellen 20/30 to 20/100) and CMT 268-375µm. 9,10,[13][14][15] BCVA at five years was 0.109±0.029 logMAR (Snellen 20/25), which is better than another study reporting outcomes of ERM surgery with ICG visualization (0.449±0.487logMAR; Snellen 20/60). 2 Dawson et al demonstrated that surgical intervention on patients with better preoperative BCVA yields a better final BCVA and patients with poorer preoperative BCVA showed a greater change in BCVA following ERM surgery.…”
Section: Discussionmentioning
confidence: 53%